2012
DOI: 10.1155/2012/349657
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Infection-Associated Complement Regulator-Acquiring Surface Protein 4 (ErpC) to Complement Resistance ofBorrelia burgdorferi

Abstract: Borrelia burgdorferievades complement-mediated killing by interacting with complement regulators through distinct complement regulator-acquiring surface proteins (CRASPs). Here, we extend our analyses to the contribution of CRASP-4 in mediating complement resistance ofB. burgdorferiand its interaction with human complement regulators. CRASP-4 (also known as ErpC) was immobilized onto magnetic beads and used to capture proteins from human serum. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 64 publications
2
45
0
Order By: Relevance
“…Regrettably, available molecular tools that were successfully engineered for gene inactivation in B. burgdorferi completely failed in B. afzelii and B. spielmanii. However, previous studies conclusively demonstrated that lipoproteins from B. burgdorferi retained their biological function and still interacted with various host proteins when ectopically produced in B. garinii G1 (13,14,47). Thus, we decided to employ this serum-sensitive B. garinii strain as a surrogate to overcome the aforementioned technical limitations and investigate CspA-mediated serum resistance of viable cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regrettably, available molecular tools that were successfully engineered for gene inactivation in B. burgdorferi completely failed in B. afzelii and B. spielmanii. However, previous studies conclusively demonstrated that lipoproteins from B. burgdorferi retained their biological function and still interacted with various host proteins when ectopically produced in B. garinii G1 (13,14,47). Thus, we decided to employ this serum-sensitive B. garinii strain as a surrogate to overcome the aforementioned technical limitations and investigate CspA-mediated serum resistance of viable cells.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm localization of native CspA orthologs on the spirochetal surface, protease accessibility assays using proteinase K (Sigma-Aldrich, Taufkirchen, Germany) were performed as previously described (11,13,47).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For B. burgdorferi, a number of plasminogen-binding proteins have been reported, including OspA (31) and OspC (32), BPBP (30), and more recently B. burgdorferi enolase (34 -36). Of note, the functionally related but genetically heterologous complement regulator-acquiring surface proteins CspA, CspZ, ErpP, ErpC, and ErpA all bind plasminogen in addition to binding various host-derived complement regulators (28,29,(63)(64)(65)(66). Other pathogenic microorganisms have proteins that also bind both plasminogen and complement regulators, such as factor H, factor H-like protein 1, factor H-related protein-1, or C4b-binding protein (23,26,27,(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%
“…The differentially regulated B. burgdorferi surface protein CspA (32)(33)(34)(35) and some of the OspE-related protein family members, including ErpA (36,37), ErpP (37), and ErpC (38,39), all act similarly by recruitment of complement regulator factor H (FH) and factor H-like protein-1 (FHL-1) or complement factor H-related proteins (CFHR), presumably to the surface of the bacterium, although the majority of studies have been performed using recombinant protein. FH, FHL-1, and the CFHRs inhibit the alternative complement cascade by cleaving C3b.…”
mentioning
confidence: 99%